Reggio Emilia 2007-2008 the golden jubilee tournament - Marin, Mihail; Garrett, Yuri (London Quality Chess, 2009)
This book celebrates fifty years of the famous Italian tournament. All the games are analysed, many of them by the players themselves: those sharing their wisdom include award-winning author Mihail Marin, rising star Ni Hua, Tournament winner Zoltan Almasi and the legendary Victor Korchnoi. In addition, photographs and entertaining stories take the reader behind the scenes at a top-class tournament
How this book was born -- How a tournament is born -- Round 1 -- Round 2 -- Round 3 -- Round 4 -- Round 5 -- Round 6 -- Round 7 -- Round 8 -- Round 9 -- In lieu of conclusion
First published in Italian by Caissa Italia
Keywords: Chess -- Tournaments